Analysis Of Database Record Compression Using The Levenstein Algorithm - Rian Syahputra (The IJICS (International Journal of Informatics and Computer Science), 2019)
Data stored in the database affects how much storage memory is used. The more data stored, the more memory will be used. To reduce memory usage it is necessary to reduce the data to be stored. The technique that can be used is data compression. Levenstein algorithm is a data compression technique that replaces the initial bits of the string, resulting in smaller compression. Levenstein algorithm is suitable for compressing data that has many repetitions.